УЗЛУКСИЗ ТАЪЛИМ ЖАРАЁНИДА ЎҚУВЧИ - ЁШЛАРНИНГ ИЖОДИЙ ФИКРЛАШ ТАФАККУРИНИ РИВОЖЛАНТИРИШНИНГ АФЗАЛЛИК ТОМОНЛАРИ - Содиқова, Д.Р. (SCIENCE and SOCIETY, 2022)
This article highlights the specific aspects of the development of creative thinking of younger students in the process of additional education.
Keywords: scientific outlook; creative thinking; contemplation; self-education; education system; intellectual; knowledge